How news reporting exacerbated the monkeypox pandemic in Spain and the US: A corpus-based news values analysis - Renping Liu; Cheng Chen (Taylor & Francis Group, 2024)
ABSTRACTMedia reporting greatly influences the civilians' mentality, which further exacerbates or mitigates outbreaks of infectious diseases, prolongs or shortens the pandemic process. Adopting corpus linguistic methods and Discursive news values analysis (DNVA) framework, this study examined the news values through key words, naming strategies and photographs in monkeypox-themed news reporting in Spanish and the US media, to analyse how they constructed the monkeypox pandemic in their news reporting, sold it to the public and exacerbated the pandemic in the two societies. The results show that the Spanish media constructed the monkeypox pandemic predominantly as an international medical event, distancing the monkeypox pandemic from the Spanish indigenous context and depriving the domestic audiences from the sense of urgency to take prevention actions. On the other hand, the US media mainly packaged the monkeypox pandemic as a political event which isolated this public health crisis from the life of the common people and hindered the US citizens' understanding of the requisite medical information about the monkeypox virus. It is concluded that the lack of indigenous focus of the Spanish media, and the excessively politicised focus of the US media are important factors that lead to the exacerbation of the monkeypox epidemic.